2017
DOI: 10.4049/jimmunol.1600787
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Promote Antiviral Immunity in Mice Infected with Influenza A Virus

Abstract: Eosinophils are multifunctional cells of the innate immune system linked to allergic inflammation. Asthmatics were more likely to be hospitalized but less likely to suffer severe morbidity and mortality during the 2009 influenza pandemic. These epidemiologic findings were recapitulated in a mouse model of fungal asthma wherein infection during heightened allergic inflammation was protective against influenza A virus (IAV) infection and disease. Our goal was to delineate a mechanism(s) by which allergic asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(194 citation statements)
references
References 67 publications
9
179
1
5
Order By: Relevance
“…Lazarevic et al, 2013). Increased neutrophils and eosinophils in T-bet À/À lungs may also play compensatory roles to other immune cells following influenza virus infection (Fujisawa, 2008;Tate et al, 2011;Hufford et al, 2012;Samarasinghe et al, 2017). All these immune responses are crucial against viral infections, yet surprisingly, the loss of T-bet did not result in marked deficiency in defence against the influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…Lazarevic et al, 2013). Increased neutrophils and eosinophils in T-bet À/À lungs may also play compensatory roles to other immune cells following influenza virus infection (Fujisawa, 2008;Tate et al, 2011;Hufford et al, 2012;Samarasinghe et al, 2017). All these immune responses are crucial against viral infections, yet surprisingly, the loss of T-bet did not result in marked deficiency in defence against the influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that H1N1 virus infection can induce the degranulation and facilitate the activation and proliferation of CD8 T cells in vitro . In this work, adoptive transfer of eosinophils from infected animals could protect the recipients against influenza challenge by enhancing antigen-specific cellular responses [114]. The combination of these immune regulatory and enhancing functions with the known effects of eosinophils on lung function requires further studies to determine the relative contributions of each activity and the regulatory role of IL-5 in these processes.…”
Section: Cytokines Induced By Immune Responses (Secondary Cytokines)mentioning
confidence: 99%
“…Eosinophils have been shown to exhibit phenotypic changes in response to signals from the extracellular matrix in murine asthma models . They can recruit Th2 CD4 + T cells, activate dendritic cells, polarize M2 macrophages cause nerve cell branching, recruit and activate CD8 T cells, and secrete nerve growth factor or eosinophil peroxidase which activate mast cells through TrkA or Mas‐related gene X2 (MrgX2) receptors, respectively. The interactions between eosinophils and other cells are just starting to be explored in humans.…”
Section: Resultsmentioning
confidence: 99%